Instrumentos musicais digitais e dispositivos para ampliação da prática musical de pessoas surdas: desenvolvimento de protótipos para criação e performance - Thiago Augusto Eugenio Guedes Reis (2024)
This dissertation aims to investigate the factors that influence the design of musical instruments and devices intended to enhance the active participation of deaf individuals in music. The research was conducted in two main stages. In the initial phase, an interdisciplinary literature review was carried out, encompassing the neuroscientific foundations of musical perception in deaf individuals and the principles of Universal Design, aiming to understand the specific needs and abilities of users. In the subsequent phase, prototypes of digital musical instruments were developed, using recycled materials, transducers, and open-source software such as Pure Data (PD) and MobMuPlat. Highlights include a synthesizer with tactile and visual feedback, and an electronic drum kit on a tablet. Additionally, a Tactile Feedback Platform and LED reflectors synchronized with percussive sounds were designed. Prototyping has also been extended to the adaptation and inclusion of commercial hardware. In collaboration with the collective "Todos Estão Surdos," these devices were subjected to evaluations in workshops and performances, revealing users' preference for low and percussive tones. Preliminary results suggest that the resources developed in this study, combining tactile and visual feedback, can be effectively employed in musical dynamics involving deaf individuals.